Prevalence of anemia in pregnancy at booking: a retrospective study at a tertiary care centre in Lucknow India - Nigar, Asma; Ahmad, Ausaf (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Anemia in pregnancy is one of the most common nutritional deficiency disorders affecting the pregnant women in the developing countries. The aim of our study was to understand the prevalence of anemia among pregnant women, and factors associated with anemia. Methods: It was a retrospective record based study conducted in pregnant women, attending antenatal clinic and emergency in the Department of Obstetrics and Gynecology at Integral Institute of Medical Sciences and Research, Luck now, Uttar Pradesh, India. Data from 422 pregnant women regarding pregnancy were collected from 1st January 2018 to 30th June 2018 by referring the records. Results: Present study included 422 pregnant females in first, second and third trimester. In the present study, majority of the pregnant women belonged to the age group of 20-25 years (49.5%) followed by age group of 26-30 years (35.5%). The prevalence rate of anemia was found to be 57.6%, with moderate anemia being the most common (44.8%). Higher proportion of anemia was found in third trimester (75.3%) followed by second trimester (16.5%). Conclusions: High prevalence (57.6%) of anemia was observed in pregnant women. We are far away from achieving our target of Anemia Mukht Bharat by 2022. There is need to create awareness among females regarding ANC visits, birth spacing and iron and folic acid supplementation during pregnancy.